Konsumsi Junk Food dengan Kejadian Dismenore pada Remaja Putri Siswa di SMA Negeri 1 Bone - Jumarni Jumarni; Sakinah Amir; Hasnidar Hasnidar (Journal of Innovative and Creativity, 2025)
This study investigates the relationship between junk food consumption and the incidence of dysmenorrhea among female adolescent students at SMA Negeri 1 Bone. The research was motivated by the high prevalence of dysmenorrhea and increasing junk food consumption among adolescents. The study aimed to analyze the correlation between junk food intake and menstrual pain severity. A quantitative approach with a cross-sectional design was employed, involving 62 female students selected through stratified random sampling. Data were collected using validated questionnaires on junk food consumption and dysmenorrhea, and analyzed using univariate and bivariate methods, including the Chi-square test. The results revealed a significant association between higher junk food consumption and increased severity of dysmenorrhea (p < 0.05). The findings indicate that students with moderate to high junk food intake are more likely to experience moderate to severe menstrual pain. The study concludes that reducing junk food consumption and promoting nutrition education are essential for improving adolescent reproductive health.